Effectiveness of Integrated Treatment Strategy for Diabetic Retinopathy in Patients with Diabetes Mellitus: A Case Report - Nargiza Normatova (Indian Journal of Forensic Medicine & Toxicology, 2020)
Vascular pathologies are considered as severe complications of diabetes mellitus, which occur veryfrequently in patients. Namely, diabetic retinopathy, being one clinical form of diabetic angiopathy, maylead to distressing socioeconomic burden like decreasing visual acuity and blindness. In the literature, manytreatment method have been described and used in many centres.We present a case of 60-year-old diabetes sufferer, who underwent combined treatment strategy includingpanretinal laser coagulation, enzyme therapy, vitreoretinal surgery and intravitreal administration of aninhibitor of angiogenesis, which was highly effective in terms of restoring visual acuity with minimalperiprocedural complications.